2014
DOI: 10.1111/ecog.00954
|View full text |Cite
|
Sign up to set email alerts
|

Tree cover at fine and coarse spatial grains interacts with shade tolerance to shape plant species distributions across the Alps

Abstract: The role of competition for light among plants has long been recognised at local scales, but its importance for plant species distributions at larger spatial scales has generally been ignored. Tree cover modifies the local abiotic conditions below the canopy, notably by reducing light availability, and thus, also the performance of species that are not adapted to low-light conditions. However, this local effect may propagate to coarser spatial grains, by affecting colonisation probabilities and local extinctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 77 publications
1
32
0
Order By: Relevance
“…We infer that reduced basal area favors the establishment of species that are otherwise excluded by competition. Other studies have described a similar relation between high tree cover, competition for light, and elevation range limits in shrub and nonwoody plant species at temperate (Nieto‐Lugilde et al, ) and tropical ecosystems (Johansson et al, ). These studies found that reductions in tree cover helped shrub species to expand their range to lower elevations.…”
Section: Discussionsupporting
confidence: 54%
“…We infer that reduced basal area favors the establishment of species that are otherwise excluded by competition. Other studies have described a similar relation between high tree cover, competition for light, and elevation range limits in shrub and nonwoody plant species at temperate (Nieto‐Lugilde et al, ) and tropical ecosystems (Johansson et al, ). These studies found that reductions in tree cover helped shrub species to expand their range to lower elevations.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, the radiation variables should first be incorporated into SDMs, seasonal variations should be accounted for and the effects of canopy and cloud cover should be included when studying understorey vegetation (Nieto‐Lugilde et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as mentioned before, the use of solar radiation as a predictor can lead to misleading interpretations, as its impact on plants might strongly depend on season, canopy structure and cloud cover. Thus, the radiation variables should first be incorporated into SDMs, seasonal variations should be accounted for and the effects of canopy and cloud cover should be included when studying understorey vegetation (Nieto-Lugilde et al 2015).…”
Section: Lightmentioning
confidence: 99%
“…In particular, interspecific differences in the ability to compete for light and in shade tolerance are considered key determinants of forest stand structure and dynamics. Microclimatic effects generated by the forest canopy buffer macroclimatic changes, and create "climatic lags" that help to maintain understorey biodiversity (De Frenne et al 2013;Nieto-Lugilde et al 2014).…”
Section: Ontogenetic Effects: Shade Tolerance From Seedlings To Adultsmentioning
confidence: 99%